Int. J. Adv. Res. Biol. Sci 2017
DOI: 10.22192/ijarbs.2017.04.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Pregnant Women’s Attitude toward Using Ultrasound in Pregnancy and its Diagnostic Value based on the Demographic Features in Amir-al-Momenin Hospital of Zabol, 2015-2016

Abstract: Ultrasound is widely used in pregnancy and it is considered as a part of the routine cares given in pregnancy. Ultrasound is also applied for screening during pregnancy. The present research aims at studying the pregnant women's attitudes toward using ultrasound in pregnancy and its diagnostic value based on the demographic variables in Amir-al-Momenin Hospital of Zabol from 2015 to 2016. The present study is a descriptive-analytical one conducted on pregnant women referring to Amir-al-Momenin Hospital of Zabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
0
1
Order By: Relevance
“…This study, consistent with research conducted in Gedeo, found that 17.3% of pregnant women believed that obstetric ultrasonography could cause congenital defects. This is higher than Jeddah’s finding (5.5%) [ 5 ] and lower than in Iran (53.3%) and Uganda (78%) [ 6 , 24 ]. This may be a result of the study’s time and the sociodemographic characteristics of the participants.…”
Section: Discussioncontrasting
confidence: 59%
“…This study, consistent with research conducted in Gedeo, found that 17.3% of pregnant women believed that obstetric ultrasonography could cause congenital defects. This is higher than Jeddah’s finding (5.5%) [ 5 ] and lower than in Iran (53.3%) and Uganda (78%) [ 6 , 24 ]. This may be a result of the study’s time and the sociodemographic characteristics of the participants.…”
Section: Discussioncontrasting
confidence: 59%